Handling missing data in randomization tests for single-case experiments: A simulation study - De, Tamal Kumar; Michiels, Bart; Tanious, René; Onghena, Patrick (Behavior research methods, 2020)
Single-case experiments have become increasingly popular in psychological and educational research. However, the analysis of single-case data is often complicated by the frequent occurrence of missing or incomplete data. If missingness or incompleteness cannot be avoided, it becomes important to know which strategies are optimal, because the presence of missing data or inadequate data handling strategies may lead to experiments no longer “meeting standards” set by, for example, the What Works Clearinghouse. For the examination and comparison of strategies to handle missing data, we simulated complete datasets for ABAB phase designs, randomized block designs, and multiple-baseline designs. We introduced different levels of missingness in the simulated datasets by randomly deleting 10%, 30%, and 50% of the data. We evaluated the type I error rate and statistical power of a randomization test for the null hypothesis that there was no treatment effect under these different levels of missingness, using different strategies for handling missing data: (1) randomizing a missing-data marker and calculating all reference statistics only for the available data points, (2) estimating the missing data points by single imputation using the state space representation of a time series model, and (3) multiple imputation based on regressing the available data points on preceding and succeeding data points. The results are conclusive for the conditions simulated: The randomized-marker method outperforms the other two methods in terms of statistical power in a randomization test, while keeping the type I error rate under control.